Student Satisfaction with Online Learning: A Multigroup Analysis - Santosa, Paulus Insap (Information Systems - Universitas Pesantren Tinggi Darul Ulum, 2022)
The Coronavirus disease 2019 pandemic “forced” students to attend online classes roughly from mid-March 2020. This situation, which caused universities, among other institutions, to deal with an overnight change in course delivery from traditional face-to-face to online mode, has resulted in many students facing difficulties. They must cope with the available infrastructure, unstable and limited Internet connection, course delivery, and their self-discipline. Male and female students may have different preferences regarding technology use. This study focused on student satisfaction with the above situation and determined whether a difference exists between male and female students using Technology Acceptance Model as the main theoretical background. Seven hypotheses were proposed and tested with the whole dataset and comparisons between the two groups. Due to the strict health protocol, an online survey was employed using Google Form to collect data. Respondents were 327 undergraduate students from one higher institution in Yogyakarta, comprising 140 male and 187 female students. The population consisted of undergraduate students who have been attending online classes since March 2022. A multigroup analysis was performed using SmartPLS 3.3.3. Results indicated no gender difference in all hypothesized relationships. The theoretical contribution can be seen from the use of Internet Quality, User Interface Quality, and Delivery Quality as the three exogenous variables of the proposed model. The practical contribution is that technology designers must pay attention to the different preferences of user groups.